A Novel miRNA Detection Method Using Loop-Mediated Isothermal Amplification - Saiwei Wu; Abdu Ahmed Abdullah Al-Maskri; Qun Li; Jiatong Liu; Sheng Cai (International Journal of Analytical Chemistry)
A novel ligation-based loop-mediated isothermal amplification has been developed for miRNA detection. Two stem-loop structure DNA linker A/B probes which hybridized with miRNA were designed to establish a rapid and ultrasensitive miRNA-LAMP system for miRNA detection. Target miR-200a was used to template the ligation of Linker A/B probes with SplintR Ligase and used as a dumbbell-shaped amplicon. By adding BIP/FIP and Bst 2.0 DNA polymerase, the LAMP reaction was carried out, which brought greatly improved amplification efficiency. The double-stranded DNA fluorescent dye EvaGreen was added for the detection of amplification product to achieve the quantification of the target miRNA. This method can detect miRNA in a linear range of seven orders of magnitude, with a detection limit of 100 fM. Therefore, this ultrasensitive miRNA-LAMP assay provides a new path for the highly sensitive quantitative analysis of miRNA, thereby bringing convenience to clinical diagnosis and prognostic research.